(3GdeMGSHI aj GdhMOGJ GdMchejI hGdeMGSHI GdbhejIs - (3eMeO GdSjO(B, (3SQGjGs ((3HjQhJ(B:s (3GdOGQ GdLGeYjI(B,s)
(3GdYdGbI Hjf GdeMGSHI GdbhejI hcd ef GdeMGSHI GdeGdjI hGdeMGSHI GdMchejI, ebheGJ eMGSHI GdONd Gdbhej Ydi GSGS eaGgje GdONd hGdGfJGL Gdbhej hGdbjeI GdeVGaI, GdGWGQ GdYGe ddeMGSHI GdbhejI Ydi eSJhi GdbWGYGJ, GdMSGHGJ GdbhejI eY hLhO GdbWGY GdMchej hbWGY GdYGe GdNGQLjs
Keywords: (3GdeMGSHI GdMchejIs; (3GdeMGSHI GdbhejIs